- 1-214-256-5804
- info@tutorpace.com

Thus a ^m = a x a x a x a x ………….to m factors.

Here, a is called the base of a^m and m is the exponent of a^m.

For example: - x^3 = x * x * x

And (-3)^6 = (-3) * (-3) *(-3) * (-3) * (-3) * (-3);

Here x and -3 are the base of x ^3 and (-3)^6 respectively and their exponents are 3 and 6.

In particular, a ^2 is called the square of a (or, a to the power 2) and a^3 is called the cube of a (or, a to the power 3).

Add the exponents (2x^2+3y^2+z^3) and (x^2 + y^3 + 3 z^3).

(2 x^2 + 3 y^2 + z^3 ) + (x^2 + y^2 + 3 z^3)

= (2 x^2 + x^2) + (3 y^2 + y^2) +(z^3 + 3 z^3) (Group the like terms)

=

(5 x^3 + 8 x^2 + 2x) + (x ^3 + 2 x^2 + 3 x.)

= (5 x^3 + x^3)+(8 x^2 + 2 x^2)+ (2 x + 3 x)

=